CERN experience and strategy for the maintenance of cryogenic plants and distribution systems. Issue 1 (November 2015) - Serio, L; Bremer, J; Claudet, S; Delikaris, D; Ferlin, G; Pezzetti, M; Pirotte, O; Tavian, L; Wagner, U
Abstract: CERN operates and maintains the world largest cryogenic infrastructure ranging from ageing installations feeding detectors, test facilities and general services, to the state-of-the-art cryogenic system serving the flagship LHC machine complex. After several years of exploitation of a wide range of cryogenic installations and in particular following the last two years major shutdown to maintain and consolidate the LHC machine, we have analysed and reviewed the maintenance activities to implement an efficient and reliable exploitation of the installations. We report the results, statistics and lessons learned on the maintenance activities performed and in particular the required consolidations and major overhauling, the organization, management and methodologies implemented.